Efficacy and safety of antithrombotic therapy with non-vitamin K antagonist oral anticoagulants after transcatheter aortic valve replacement: a systematic review and meta-analysis. (November 2021) - An, Qing; Su, Shuwen; Tu, Yan; Gao, Lingfeng; Xian, Gaopeng; Bai, Yujia; Zhan, Qiong; Xu, Xingbo; Xu, Dingli; Zeng, Qingchun
Objective: A meta-analysis was performed to compare the efficacy and safety of antithrombotic therapy with non-vitamin K antagonist oral anticoagulants (NOACs) versus standard care in patients after successful transcatheter aortic valve replacement (TAVR). Methods: A systematic search of PubMed, Cochrane Central Register of Controlled Trials, and EMBASE databases andClinicalTrials.gov website (through 21 October 2020) was performed. Risk ratios (RRs) with 95% confidence intervals (CIs) for all outcomes were calculated using random-effects models. Results: Twelve studies (two studies were randomized controlled trials) comprising 6943 patients were included (5299 had indications for oral anticoagulation (OAC) and 1644 had none). No significant differences were found between NOACs and the standard care in the incidences of all stroke, a composite endpoint, and major/life-threatening bleeding. NOACs were associated with lower all-cause mortality than vitamin K antagonists (VKAs) in post-TAVR patients with indications for OAC after more than 1 year of follow-up [RR = 0.64; 95% CI, (0.42, 0.96); p  = 0.03], whereas NOACs exhibited poor outcomes than antiplatelet therapy (APT) in patients without indications for OAC [RR = 1.66; 95% CI, (1.12, 2.45); p  = 0.01]. In the prevention of valve thrombosis, NOACs and VKAs were not significantly different in patients with indications for OAC [RR = 0.66; 95% CI, (0.24, 1.84); p  = 0.43], whereas NOACs were better than APT in patients without indications for OAC [RR = 0.19; 95% CI, (0.04, 0.83); p = 0.03]. Conclusions: In patients with indications for OAC, post-TAVR antithrombotic therapy with NOACs was more favorable due to its lower all-cause mortality after more than 1 year of follow-up. In those without indications for OAC, NOACs presented poorer outcomes due to its higher all-cause mortality.